Microtensile Bond Strenh Between Indirect Composite Resin Inlays and Dentin: Effect of Cementation Strategy and Mechanical Aging - Prochnow, Emilia Pithan; Amaral, Marina [UNESP]; Bergoli, Cesar Dalmolin; Silva, Tatiana Bernardon; Saavedra, Guilherme [UNESP]; Valandro, Luiz Felipe (Quintessence Publishing Co Inc, 2014)
Purpose: To evaluate the microtensile bond strength of indirect resin composite inlays to dentin using two cementation strategies, before and after mechanical aging.Materials and Methods: Standardized inlay cavities (bucco-lingual width: 3 mm; depth: 4 mm) were prepared in 32 human premolars. The teeth were embedded in self-curing acrylic resin up to 3 mm from the cementoenamel junction, impressions were made using a polyvinyl siloxane material, master dies were obtained using type 4 stone, and inlay composite resin restorations were fabricated (Sinfony, 3M ESPE). The teeth were randomly allocated into 4 groups according to the cementation strategy (conventional [C] and simplified [S]) and aging (mechanical cycling [MC] and not aged): C[G1]: Adper Single Bond + RelyX ARC without aging; CMC[G2]: conventional cementation + mechanical cycling (10(6) cycles, 88 N, 4 Hz, 37 degrees C); S[G3]: self-adhesive resin cement (RelyX U-100) without aging; SMC[G4] self-adhesive cementation + mechanical cycling. Intaglio surfaces of composite inlays were treated by tribochemical silica coating in G1 and G2, while G3 and G4 received no surface treatment. Non-aged specimens were stored in a moist environment at ca 37 degrees C for the same period as MC (3 days). Non-trimmed beam specimens (bonding area = 1 mm(2)) were produced by serial cutting, and microtensile testing was performed (0.5 mm/min).Results: Two-way ANOVA showed that the microtensile bond strength was affected only by cementation strategy (p < 0.0001). Tukey's test showed that groups G1 (35.1 +/- 9.1) and G2 (32.7 +/- 10.7) presented significantly higher bond strength values than G3 (8.7 +/- 6.3) and G4 (5.2 +/- 4.6).Conclusion: The use of a conventional adhesive technique and tribochemical silica coating resulted in higher mu TBS than the one-step simplified cementation, even after mechanical cycling.
Keywords: adhesion; cementation; indirect resin; mechanical cycling; microtensile bond strength